Changes in Corporate Governance Associated with the Revelation of Internal Control Material Weaknesses and Their Subsequent Remediation* - Johnstone, Karla; Li, Chan; Rupley, Kathleen Hertz (Contemporary Accounting Research, 2011)
The revelation of material negative events about a firm, including issues such as fraud, restatements, or internal control material weaknesses (ICMWs), may destabilize the firm’s corporate governance equilibrium as it works to remediate the event or effects thereof. Prior research investigates the association between the revelation of fraud and restatements and both board and management turnover. We extend that research, proposing and testing a conceptual model of the process that firms use to remediate negative events in general and ICMWs specifically, with a focus on the role of governance structure changes. Using a sample of 733 firms revealing an ICMW compared to 3,602 firms with unqualified internal control reports, results reveal a positive association between disclosure of ICMWs and subsequent turnover of members of boards of directors, audit committees, and top management. Focusing on the ICMW sample and comparing the 511 firms that remediate their ICMWs to the 222 firms that do not, results illustrate a positive association between remediation of ICMWs and improvements in the characteristics of boards of directors, audit committees, and top management. Data Availability: Data are publicly available from sources identified in the paper.